Transcranial direct current stimulation effects on neural processing in post‐stroke aphasia - Darkow, Robert (Hum Brain Mapp, 2016)
Non‐invasive transcranial direct current stimulation (tDCS) can enhance recovery after stroke. However, fundamental knowledge about how tDCS impacts neural processing in the lesioned human brain is currently lacking. In the present study, it was investigated how tDCS modulates brain function in patients with post‐stroke language impairment (aphasia). In a cross‐over, randomized trial, patients named pictures of common objects during functional magnetic resonance imaging (fMRI). Concurrently, excitatory (anodal‐) or sham‐tDCS (1 mA, 20 min, or 30 s, respectively) was administered to the left primary motor cortex, a montage with demonstrated potential to improve aphasic language. By choosing stimuli that could reliable be named by the patients, the authors aimed to derive a pure measure of stimulation effects that was independent of treatment or performance effects and to assess how tDCS interacts with the patients' residual language network. Univariate fMRI data analysis revealed reduced activity in domain‐general regions mediating high‐level cognitive control during anodal‐tDCS. Independent component functional network analysis demonstrated selectively increased language network activity and an inter‐correlated shift from higher to lower frequency bands, indicative of increased within‐network communication. Compared with healthy controls, anodal‐tDCS resulted in overall “normalization” of brain function in the patients. These results demonstrate for the first time how tDCS modulates neural processing in stroke patients. Such information is crucial to assure that behavioral treatments targeting specific neural circuits overlap with regions that are modulated by tDCS, thereby maximizing stimulation effects during therapy. Hum Brain Mapp 38:1518–1531, 2017. © 2016 Wiley Periodicals, Inc.